2021
DOI: 10.3390/jmse9101113
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Transdisciplinary Framework to Overcome Energy Efficiency Barriers in Shipbuilding: A Case Study for an Iranian Shipyard

Abstract: Through a systematic literature review and a holistic perspective, the study proposes a conceptual transdisciplinary framework to overcome energy efficiency barriers during the shipbuilding phase. The process of the proposed transdisciplinary framework consists of five steps of “goal formation”, “system analyzing”, “scenario construction”, “multi-criteria decision making assessment” and “strategy building” to identify and rank the energy efficiency barriers during ship construction based on decision makers’ pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 120 publications
(213 reference statements)
0
21
0
Order By: Relevance
“…IPCC (Intergovernmental Panel on Climate Change) [23] classified barriers to energy efficiency as technological innovation, prices, finance, trade and environment, market structure, institutional framework, information provision and social, cultural and behavioral norms and standards, and Fleiter et al [24] classified barriers to energy efficiency as twelve different characteristics. In addition, empirical studies such as Thollander and Ottson [14], Cagno and Trianni [25], Dixon et al [26], Nehler et al [27], Lane et al [28] and Vakili et al [13] have identified and classified barriers to energy efficiency in various industries and in different categories.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…IPCC (Intergovernmental Panel on Climate Change) [23] classified barriers to energy efficiency as technological innovation, prices, finance, trade and environment, market structure, institutional framework, information provision and social, cultural and behavioral norms and standards, and Fleiter et al [24] classified barriers to energy efficiency as twelve different characteristics. In addition, empirical studies such as Thollander and Ottson [14], Cagno and Trianni [25], Dixon et al [26], Nehler et al [27], Lane et al [28] and Vakili et al [13] have identified and classified barriers to energy efficiency in various industries and in different categories.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to improve energy efficiency in the maritime cluster, a policy in the marine energy sector is crucial, and it is invoked to justify the policy in the maritime energy sector. To reduce the carbon footprint of the maritime sector, a holistic systemic policy and a broader vision (life-cycle perspective) must be taken into account [13].…”
Section: Barriers To Energy Efficiency In Shippingmentioning
confidence: 99%
See 3 more Smart Citations